Аналіз сучасних засобів розробки компонентів інформаційної системи продажу цифрової техніки - Ізюмський, М. О. (ХНУРЕ, 2023)
The article examines the use of modern means of developing components of the information system for the sale of digital equipment. Various technologies were analyzed and ultimately MySQL and Razor were chosen as the most acceptable options. The article provides a detailed overview of the advantages and disadvantages of different technologies, which may be useful for software developers working on similar projects. Overall, this article offers valuable information for anyone interested in modern software development tools and their applications